Restorative Justice Framework for Underage Drug Abusers to Face Long-Term and Societal Challenges - Alhakim, Abdurrakhman; Rusdiana, Shelvi; Hutauruk, Rufinus Hotmaulana (Jurnal Wawasan Yuridika, 2023)
Youth development has always been an important aspect in the fight against drug abuse, which includes the effort in dealing with underage drug abusers to help them reflect and get back to society. Using normative legal research method, this research dives deep into the challenges facing underage drug abusers on their way back to society and how these challenges impact their future involvement with drugs and their ability to function normally. Through statutory approach, this research finds the possible normative construction to provide a concrete framework of restorative justice. With the restorative justice approach, societal challenges facing underage drug abusers such discriminations, prejudice, and labelling can be met with solutions that provide implementation during the process of rehabilitation and after it.